1998
DOI: 10.1046/j.1471-4159.1998.70062227.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic Gene Locus

Abstract: Messenger RNAs and the cognate gene(s) entions require the protein machinery for ACh synthesis coding choline acetyltransferase (ChAT) and the vesicuand sequestration to be expressed in particular neurons lar acetyicholine transporter (VAChT) have been cloned at particular locations, including motor neurons, parafrom mammals and several other animal classes in the sympathetic autonomic neurons, brainstem reticular last decade. These have provided molecular tools for inactivating neurons, and basal forebrain pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(127 citation statements)
references
References 10 publications
6
121
0
Order By: Relevance
“…It has been proposed, although not proven, that VAChT, along with synaptophysin (7), is trafficked from the trans-Golgi network (TGN) to the plasma membrane via the constitutive secretory pathway, then from the plasma membrane to an endosomal compartment, and finally from the endosomal compartment to SLMVs (6).…”
mentioning
confidence: 99%
“…It has been proposed, although not proven, that VAChT, along with synaptophysin (7), is trafficked from the trans-Golgi network (TGN) to the plasma membrane via the constitutive secretory pathway, then from the plasma membrane to an endosomal compartment, and finally from the endosomal compartment to SLMVs (6).…”
mentioning
confidence: 99%
“…ChAT and VAChT are synthetic enzymes required for the synthesis and uptake of acetylcholine into synaptic vesicles, respectively [5]. The ChAT gene locus contains the entire sequence of VAChT cDNA, enabling transcription of VAChT and ChAT mRNA from the same or neighboring promoters [6].…”
Section: Discussionmentioning
confidence: 99%
“…The VAChT coding region is contained within the ChAT gene locus [6]. Transcription of both genes is controlled by the same or neighbouring promoters, which thereby coordinate expression of the two proteins, both of which are required to establish a cholinergic phenotype [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ChAT gene is part of a more complex genetic locus also coding for the vesicular acetylcholine transporter (VAChT) which packages transmitter into synaptic vesicles. 24 The genomic organization of these two distinct but related genetic functions is unique, and has been conserved from Drosophila to humans. 24 Recent animal studies clearly show that through a cascade of events stressful experiences can mediate neuronal plasticity by direct action upon the genetic expression of cholinergic muscarinic receptors in the relative long-term.…”
Section: Why the Cholinergic System Can Be Important In Panic Attacksmentioning
confidence: 99%
“…24 The genomic organization of these two distinct but related genetic functions is unique, and has been conserved from Drosophila to humans. 24 Recent animal studies clearly show that through a cascade of events stressful experiences can mediate neuronal plasticity by direct action upon the genetic expression of cholinergic muscarinic receptors in the relative long-term. Kaufer and colleagues 25 showed that acute stress of even moderate intensity (eg, a single session of 4 min forced swimming in mice)-as well as inhibitors of acetylcholinesterase (AChE)-produce a transient increase in the amount of released ACh in corticohippocampal areas, independent of the pituitary-adrenocortical axis.…”
Section: Why the Cholinergic System Can Be Important In Panic Attacksmentioning
confidence: 99%